Seasonal changes in the population structure of dominant planktonic copepods collected using a sediment trap moored in the western Arctic Ocean - Matsuno, Kohei; Yamaguchi, Atsushi; Fujiwara, Amane; Onodera, Jonaotaro; Watanabe, Eiji; Harada, Naomi; Kikuchi, Takashi (Journal of natural history, 2015)
Winter ice cover of the Arctic Ocean makes year-round zooplankton sampling by plankton net a difficult task. Therefore, the collection of copepods with a sediment trap can be a powerful tool. In the present study, we analysed the seasonal changes in the population structures of five dominant planktonic copepods (Oncaea parila , Calanus hyperboreus , Metridia longa , Paraeuchaeta glacialis and Heterorhabdus norvegicus), which were collected using a sediment trap rotated at 10–15 day intervals moored at 184–260 m in the Northwind Abyssal Plain (75°00′N, 162°00′W) of the western Arctic Ocean from October 2010 to September 2012. Oncaea parila C6F with egg sacs occurred throughout the year, and the total abundance and composition of early copepodid stages (C1−C3) had two peaks each year. Calanus hyperboreus was dominated by C6F throughout the year, and their maturation was observed during February to May. Metridia longa C6F had a clear seasonality in lipid accumulation and gonad maturation: high lipid accumulation was observed from October to February, whereas gonad maturation occurred from March to September. Paraeuchaeta glacialis C6F also showed seasonality in lipid accumulation and gonad maturation, although their seasonal patterns varied from those of M. longa : high lipid individuals were abundant from February to April and mature individuals dominated from October to November. Heterorhabdus norvegicus showed seasonal changes in population structure as well: C1, C5, and C6M dominated from April to May, November to February and August to October, respectively. The life cycle patterns of these species are compared with those reported from other areas. While the results obtained by a sediment trap are inevitably subject to collection bias (i.e. passive collection at a fixed depth), a sediment trap should be considered as a powerful tool for the evaluation of the life cycle of planktonic copepods, especially in ice-covered oceans.